HUBUNGAN MINAT BELAJAR IPA SISWA KELAS V SD NEGERI 2 PELEMKEREP TERHADAP HASIL BELAJAR SELAMAPEMBELAJARAN DARING - Dicky Ahmad Nor Sidiq; Fina Fakhriyah; Siti Masfuah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
The purpose of this study was to analyze the students' interest in learning science class V SD Negeri 2 Pelemkerep during online learning and to analyze the relationship between interest in learning science and learning outcomes for students at SD Negeri 2 Pelemkerep during online learning. This study uses a quantitative approach to the type of correlation research. Correlation research is a study conducted to find the level of relationship between variables and to find out how big the relationship between each variable is used. This research was conducted in class V SD Negeri 2 Pelemkerep Jepara. The independent variable in this study is the interest in learning science, while the dependent variable is the result of learning science. The data analysis technique used is the product moment correlation test and one sample t test. The results of this study indicate that (1) there is a relationship between interest in learning science and learning outcomes of students at SD Negeri 2 Pelemkerep during online learning with a correlation coefficient value of 0.905 in the very strong category and (2) the average interest in learning science for students at SD Negeri 2 Pelemkerep during online learning> 50% with an average value of the questionnaire on learning interest of 86.04 and an average value of learning outcomes in science learning of 83.78. Based on the results of the calculation, the average percentage of the answers to the questionnaire on the students' interest in learning science as a whole was 54.36%, meaning that most students had an interest in learning science.